Pandemi Covid, penunjang atau penghambat bagi para peneliti dunia medis - Adi Nugroho, Prasetyo (FPPTI Jawa Tengah, 2021)
The corona virus restrain the movement of people. Higher education has also been affected, especially academics. The repository as a data provider is expected to be a solution to data provider problems during the pandemic. This study aims to analyze whether the repository of scientific papers has an effect on improving the scientific work of medical academics or not. This study uses a quantitative method with a bibliometric approach. The sample of this study is the repository of scientific papers at Gadjah Mada University. The sample is divided into two, scientific papers contain the keyword